Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fmicb.2017.00138
|View full text |Cite
|
Sign up to set email alerts
|

Feeding a High Concentration Diet Induces Unhealthy Alterations in the Composition and Metabolism of Ruminal Microbiota and Host Response in a Goat Model

Abstract: There is limited knowledge about the impact of long-term feeding a high-concentrate (HC) diet on rumen microbiota, metabolome, and host cell functions. In this study, a combination of mass spectrometry-based metabolomics techniques, 454 pyrosequencing of 16S rDNA genes, and RT-PCR was applied to evaluate the changes of ruminal microbiota composition, ruminal metabolites, and related genes expression in rumen epithelial cells of lactating goats received either a 35% concentrate diet or a 65% concentrate diet fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 64 publications
9
64
1
Order By: Relevance
“…Previous studies showed that a long‐term HG diet appeared to disrupt the balance of the ruminal microbiota and affect the rumen health of dairy cattle and goats (Hua et al, ; Wetzels, et al, ). In the present study, the HG diet increased the richness of bacterial communities of jejunal mucosa, but it seemed to have no apparent effect on the richness of bacterial communities of ileal mucosa, with no significant between‐group difference observed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a long‐term HG diet appeared to disrupt the balance of the ruminal microbiota and affect the rumen health of dairy cattle and goats (Hua et al, ; Wetzels, et al, ). In the present study, the HG diet increased the richness of bacterial communities of jejunal mucosa, but it seemed to have no apparent effect on the richness of bacterial communities of ileal mucosa, with no significant between‐group difference observed.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial communities are crucial for the degradation of complex feeds into volatile fatty acids (VFAs) and the synthesis of vitamins and protein for ruminants' health and production performance (Krause et al 2003;Zilber-Rosenberg and Rosenberg 2008). Many factors affect the ruminal microbial community, such as host (Malmuthuge and Guan 2017), heredity (Paz et al 2016), diet (Hua et al 2017), disease (Ma et al 2018), physical stage (Zhu et al 2017), age (Jami et al 2013) or additives (Uyeno et al 2015), and diet plays a dominant role in shaping the ruminal microbial community and deciding the ruminal fermentation patterns. Concentrate-rich or forage-based diets are dominated by starch-degrading amylolytic bacteria or fibrolytic bacteria in rumen, which mainly degrade starch or fiber and produce a substantial amount of propionate or acetate, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 252 kcal are necessary to produce 1 mol of acetate, compared to 62 kcal net gain to produce propionate [28], which also release free hydrogens used to produce methane by archaea (methanogens). We observed a reduction of Acetitomaculum, an important acetogenic bacterial genus, which utilizes monosaccharides to produce acetate, and is often found when cattle are fed high grain diets [29]. We also observed a reduction of the Acidaminococcus genus, which have acetate as major end-product [30].…”
Section: Discussionmentioning
confidence: 56%